IMPACT OF VARIOUS SLOT-POLE COMBINATIONS ON AN IN-WHEEL BLDC MOTOR PERFORMANCE - (:unkn) unknown (My University, 2017)
0

In this study, the optimum design of a brushless DC (BLDC) motor which is used for in-wheel light electric vehicle (LEV) propulsion is presented. The optimization work is mainly based on different slot-pole numbers which give a substantial performance improvement for that certain application. An outer rotor, 2.5kW, 150V BLDC motor which is widely implemented in light electric vehicle traction is selected. Finite Element Analysis (FEA) of the target motor design is conducted for various slot-pole combinations. By using the captured design data, the optimized motor is manufactured and tested. The test and simulation results are compared with each other to investigate the optimization approach.
Keywords: Mühendislik, Elektrik ve Elektronik